Mining Matters: Natural Resource Extraction and Local Business Constraints - Ralph De Haas; Steven Poelhekke (Tinbergen Institute, 2016)
We estimate the impact of local mining activity on the business constraints experienced by 22,150 firms across eight resource-rich countries. We find that with the presence of active mines, the business environment in the immediate vicinity (<20 km) of a firm deteriorates but business constraints of more distant firms relax. The negative local impact of mining is concentrated among firms in tradeable sectors whose access to inputs and infrastructure becomes more constrained. This deterioration of the local business environment adversely affects firm growth and is in line with a natural resource curse at the sub-national level.
Keywords: L16; L25; L72; O12; O13; Q30; 330; Mining; natural resources; business environment